CLINICAL AND PHARMACOECONOMIC ASPECTS OF ACTIVE CONTROLLED ANTI-INFLAMMATORY THERAPY OF RHEUMATOID ARTHRITIS, BASED ON THE PRINCIPLES OF THE «TREAT-TO-TARGET» STRATEGY: CURRENT STATE OF THE ISSUE - S.B. BEKMURODZODA; YO.U. SAIDOV; KH.R. MAKHMUDOV (Avicenna Tajik State Medical University, 2019)
The review presents a detailed analysis and assessment of current views on the fundamental issues of the therapy of rheumatoid arthritis (RA) within the framework of the "treat-to-target" (T2T) strategy. The most significant principles of the strategy are the focus on preservation the patient's quality of life, careful monitoring of the RA treatment process, and the active involvement of the patient in the treatment process. The results of the longterm study of the main issues related to the RA problem indicate that the cardinal improvement in the prognosis of the disease depends not only on the widespread use of innovative and often expensive drugs but more on the revision and improvement of traditional approaches and treatment strategies, and the disease in general. An analysis of the literature shows that the optimization of RA therapy within the framework of the T2T strategy dictates the need for full clinical and economic research aimed at finding the most effective and economically benign treatment regimens for the disease